(untitled) (Economic studies journal, 2025)
The study aimed to identify the effect of regulatory genes on organizational politicization in the Faculty of Economics, Ajilat - University of Zawia, and then determine the effect between regulatory genes in its dimensions (decision-making - organizational structure - incentives - information). The study was designed based on the descriptive analytical approach, and the study community represented the faculty members of the Faculty of Economics, Ajilat - University of Zawia, numbering 143 faculty members, where a questionnaire was designed with three axes (demographic information, dimensions of regulatory genes, and organizational politicization). The study concluded that there is a statistically significant effect of regulatory genes on organizational politicization, and that the dimension of decision-making and organizational structure had a good effect, unlike the dimension of incentives and information, the effect was simple. The study recommended increasing attention to the concept of regulatory genes for organizations and the necessity of reducing the phenomenon of organizational politicization behavior in organizations.